In what context and by which mechanisms can creative arts interventions improve wellbeing in older people? A realist review protocol [version 2; peer review: 2 approved] - Geoff Wong; Anne Ferrey; Alexandra Caulfield; Jeremy Leslie-Spinks; Nia Roberts; Trish Greenhalgh; Helle Mölsted Alvesson (NIHR Open Research)
Background In recent years, there has been growing interest at national and international policy level in the potential of creative arts to support individual and community wellbeing. Creative arts encompass a wide range of activities, including performing arts, visual arts, design and craft, literature, culture and digital and electronic arts. Participation in creative arts has been linked to lower mental distress, increased social connection, improved quality of life, personal growth and empowerment. Despite this, it remains unclear exactly how participation in creative arts interventions can improve wellbeing in older individuals. This realist review aims to synthesize evidence on how elements of creative arts interventions improve wellbeing amongst older people, in particular when, how, for whom and to what extent they work. Methods and analysis This review will follow the RAMESES (Realist And Meta-narrative Evidence Syntheses: Evolving Standards) quality standards and Pawson’s five iterative stages to locate existing theories, search for evidence, select literature, extract data, and draw conclusions. It will be guided by stakeholder engagement with policymakers, practitioners, commissioners, and people with lived experience. A realist approach will be used to analyse data and develop causal explanations, in the form of context-mechanism-outcome-configurations (CMOCs), which explain how creative arts interventions impact wellbeing in older people. The CMOCs will be organised into one or more programme theories. Our refined programme theory will then be used to develop guidance for service providers of creative arts who want to use their services to improve wellbeing of older people. Ethics and dissemination This research will comply with the UK Policy Framework for Health and Social Care Research. Dissemination will be guided by our stakeholder group, building on links with policymakers, commissioners, providers, and the public. A final stakeholder event focused on knowledge mobilisation will aid development of recommendations. PROSPERO registration CRD42024580770.